Reactividad de compuestos aromáticos en combustión con oxígeno atómico (2007)
ABSTRACT: A systematic analysis of the reaction of a series of aromatic hydrocarbons (benzene, naphthalene, anthracene, phenanthrene, pyrene and naphthalene) with atomic oxygen O( 3 P) and the following hydrogen migration is presented. Electronic structure calculations were carried out using the B3LYP density functional theory method with 6311G( d) bases set using the commercial package, Gaussian_03. A total of 34 reactions were evaluated: seventeen O( 3 P) additions to aromatic hydrocarbons, and seventeen hydrogen migrations. We used the B3LYP/6311G( d) information to calculate thermal rate constants and kinetic parameters for each reaction using Transition State Theory (TST) with onedimensional Eckart tunneling correction only for addition reactions. We also evaluated the variation of the reaction free energy (DG rxn ) with the temperature.